2021
DOI: 10.1021/acs.iecr.1c02101
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Continuous Astaxanthin Isomerization in Subcritical Ethanol

Abstract: Recent studies have shown that Z-isomers of astaxanthin have greater bioavailability and biological activity than the all-E-isomer. Hence, it is important to develop efficient and practical Z-isomerization methods. This study attempted to establish a continuous-flow isomerization system for (all-E)-astaxanthin in subcritical ethanol. Specifically, the effects of temperature, pressure, time, and addition of antioxidants and a natural catalyst, allyl isothiocyanate, on the Z-isomerization and degradation were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 40 publications
2
29
0
Order By: Relevance
“…The rate of formation of (mono-Z)astaxanthin decreased in the order of 13Z-> 9Z-> 15Z-isomers. This trend is similar to our recent studies on the thermal isomerization of (all-E)-astaxanthin in organic solvents, [29,30] which can be explained in terms of the differences in the potential and activation energies of the mono-Z-isomers, that is, their relative potential energies decrease in the order of 15Z-> 13Z-> 9Zisomers, and the magnitude of the activation energy of isomerization from the all-E-isomer to individual mono-Z-isomer decreases in the order of 9Z-> 13Z-> 15Z-isomers. [31,32] The reason for the small amount of the 15Z-isomer despite its low activation energy is thought to be its high potential energy, which makes the 15Z-isomer thermodynamically unstable.…”
Section: Effect Of Temperature On Sc-co 2 Extractionsupporting
confidence: 91%
See 2 more Smart Citations
“…The rate of formation of (mono-Z)astaxanthin decreased in the order of 13Z-> 9Z-> 15Z-isomers. This trend is similar to our recent studies on the thermal isomerization of (all-E)-astaxanthin in organic solvents, [29,30] which can be explained in terms of the differences in the potential and activation energies of the mono-Z-isomers, that is, their relative potential energies decrease in the order of 15Z-> 13Z-> 9Zisomers, and the magnitude of the activation energy of isomerization from the all-E-isomer to individual mono-Z-isomer decreases in the order of 9Z-> 13Z-> 15Z-isomers. [31,32] The reason for the small amount of the 15Z-isomer despite its low activation energy is thought to be its high potential energy, which makes the 15Z-isomer thermodynamically unstable.…”
Section: Effect Of Temperature On Sc-co 2 Extractionsupporting
confidence: 91%
“…In fact, we have recently demonstrated that astaxanthin is degraded in a short time by heating above 140 °C. [30] On the other hand, many studies have demonstrated that the extraction efficiency of lipid-soluble components, such as triacylglycerols, decreases at temperatures above 80 °C. [33][34][35][36] However, for astaxanthin, adonirubin, and adonixanthin, the recovery rates showed an increasing trend up to 120 °C.…”
Section: Effect Of Temperature On Sc-co 2 Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predominant astaxanthin Z -isomers in Z-AST-D were the 9 Z - and 13 Z -isomers, representing 18.5% and 38.4%, respectively, of the total astaxanthin content. Moreover, the 15 Z -isomer and three unidentified Z -isomers (possibly the di- Z -isomers [ 19 , 20 , 21 , 22 ]) were also present. The absorption spectra of astaxanthin isomers are shown in Figure 1 b.…”
Section: Resultsmentioning
confidence: 99%
“… ( a ) Normal-phase HPLC chromatograms of an (all- E )-astaxanthin-rich diet (E-AST-D; total Z -isomer ratio = 3.2%) and a ( Z )-astaxanthin-rich diet (Z-AST-D; total Z -isomer ratio = 84.4%) and ( b ) absorption spectra of peaks a–c and (all- E )-, (9 Z )-, (13 Z )-, and (15 Z )-astaxanthin. Peaks a–c were tentatively identified as astaxanthin Z -isomers [ 19 , 20 , 21 , 22 ]. …”
Section: Resultsmentioning
confidence: 99%